Determination of Optimum Material Usage in Sandwich Panel to Resist Higher Flexural Strength - Nur Alyaa Rosman,; Farah Husna Mohd Hafez,; Farhani Husna Azhar,; Suhaila Sahat, (Multidisciplinary Applied Research and Innovation, 2026)
Sandwich panels are known for their lightweight structure and impressive strength, making them useful in many construction and engineering applications. However, there is limited research on the use of affordable and readily available materials, such as plywood and foam, in sandwich panel construction, especially in understanding how these materials perform under flexural loads. In this project, we explore the performance of sandwich panels made with plywood as the outer layers and a foam core in between. The main aim is to examine the behavior of these panels under bending loads and to understand how core thickness affects their strength and flexibility. Experiments were carried out using a three-point bending test setup with commonly available plywood and rigid foam. The results indicated improvements in both stiffness and strength of the panels with changes in design. Typical failure patterns, such as increased deflection and material distortion under load, suggest deformation concentrated in the core and face layers were observed. Overall, the plywood-foam sandwich panels demonstrated good performance and appear promising as a lightweight option for structural use. This research highlights the potential of simple, easily accessible materials in modern construction solutions.